Simple modification to improve reliability of copro-DNA examinations for diagnosing Echinococcus multilocularis infections in red foxes. (2020) - Irie, T.; Ito, T.; Kouguchi, H.; Uraguchi, K.
Abstract: Epidemiological studies of Echinococcus multilocularis infections in definitive hosts require a reliable and economic diagnostic method. In this study, the current copro-DNA examination technique was modified by increasing the faecal amounts tested and adding a step to neutralize the faeces before DNA extraction. Reliability of the modified method was evaluated using rectal faecal samples from red foxes and comparing them with intestinal worms detected using the sedimentation and counting technique (SCT) following necropsy. The modified copro-DNA examination method demonstrated 93.9% sensitivity (138/147) on the SCT. Its detectability increased depending on the worm burden, and the sensitivity was 100% in cases harbouring over 1000 worms. From 111 SCT-negative cases, six (5.4%) were copro-DNA-positive, and all were confirmed as E. multilocularis via sequencing analysis. Five of the remaining 105 SCT-negative cases (4.8%) retained polymerase chain reaction (PCR) inhibitors in the extracted solution, suggesting that approximately 5% of the red fox faeces retained these inhibitors after treatment with the present copro-DNA extraction method. Although further evaluation is needed for faeces deposited in the wild, the present copro-DNA examination technique will help monitor the E. multilocularis prevalence in definitive hosts. When used for detailed evaluations of endemicity (e.g. changes in infection pressure or spread in non-endemic areas), the absence of PCR inhibitors should be confirmed, and multiple trials on faecal subsamples are recommended.